Penggunaan Beberapa Tingkat Serat Kasar dalam Ransum Itik Jantan Sedang Bertumbuh - Sutrisna, Rudy (Jurnal Penelitian Pertanian Terapan, 2011)
This research was conducted to determine the effect of crude fiber level in rations to feed consumption, body weight, body weight gain, carcass weight, breast weight and thigh weights male duck. Male ducks 3 weeks old were divided into four treatments, each treatment ration is repeated four times using four ducks each replication. Ration of treatment given to duck experiment with the level of crude fiber 5, 10, 15, and 20%. Treatment rations containing protein (16%) and ME (2600 kcal/kg). The main source of crude fiber in the diet is fine bran. Data were analyzed using completely randomized design direction, then the test with Duncan Multiple Range Test. The level of crude fiber significantly affect (P<0.05) on average feed intake, body weight, body weight gain, carcass weight and breast weight male duck. Keywords: Male ducks, Crude fiber, Carcas